2024
DOI: 10.3390/photonics11030203
|View full text |Cite
|
Sign up to set email alerts
|

Creating an Array of Parallel Vortical Optical Needles

Paulius Šlevas,
Sergej Orlov

Abstract: We propose a method for creating parallel Bessel-like vortical optical needles with an arbitrary axial intensity distribution via the superposition of different cone-angle Bessel vortices. We analyzed the interplay between the separation of individual optical vortical needles and their respective lengths and introduce a super-Gaussian function as their axial profile. We also analyzed the physical limitations to observe well-separated optical needles, as they are influenced by the mutual interference of the ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
0
0
Order By: Relevance
“…Prior to this longitudinal distance, overlapping of adjacent Bessel rings occurs, as evident from Figure 5e. Such features were earlier observed for both zero-order and high-order Bessel beams [25,26]; the authors observed that the complete radial separation between adjacent Bessel beams depends on the longitudinal distance of Bessel beams. Contrastingly, in case of the 800 µm period grating, it was observed that the three wellseparated Bessel beams appear only beyond a longitudinal distance of 400 µm.…”
Section: Resultssupporting
confidence: 57%
“…Prior to this longitudinal distance, overlapping of adjacent Bessel rings occurs, as evident from Figure 5e. Such features were earlier observed for both zero-order and high-order Bessel beams [25,26]; the authors observed that the complete radial separation between adjacent Bessel beams depends on the longitudinal distance of Bessel beams. Contrastingly, in case of the 800 µm period grating, it was observed that the three wellseparated Bessel beams appear only beyond a longitudinal distance of 400 µm.…”
Section: Resultssupporting
confidence: 57%
“…High-order vectorial polarization states have also been widely investigated [4,5]. In contrast to the conventional linearly polarized beam, CVBs possess strong longitudinal/transverse field components in focusing [6][7][8][9][10], giving rise to many intriguing phenomena such as spin-orbit interaction [11], optical needles [12], and the topological structure of light [13][14][15][16][17], as well as a variety of applications including optical trapping [18][19][20][21], optical lithography [22,23], and optical micro-fabrication [24,25].…”
Section: Introductionmentioning
confidence: 99%